EIF3B affects the invasion and metastasis of hepatocellular carcinoma cells via the TGFBI/MAPK/ERK pathway - Ling Wang; Chuanzhong Huang; Wansong Lin; Zhifeng Zhou; Jieyu Li; Mingshui Chen; Lingyu Zhang; Yunbin Ye (Annals of Hepatology)
Introduction and Objectives: To study the effect of eukaryotic initiation factor 3B (EIF3B) on the invasion and migration of hepatocellular carcinoma (HCC) and its potential mechanism. Materials and Methods: The clinical significance of EIF3B expression was studied with The Cancer Genome Atlas (TCGA) and Gene Expression Profiling Interaction Analysis datasets. Immunohistochemical staining and western blotting were used to examine EIF3B expression in cell lines and tissues from HCC patients. The scratch assay and transwell assay were used to measure the invasion and metastasis of different HCC cell lines in vitro. The molecular mechanism of EIF3B was determined using RNA-seq and identification of dysregulated signaling pathways. Western blotting was used to verify the alterations of EIF3B signaling functioned in the promotion of HCC progression. Results: Elevated expression of EIF3B in HCC correlated significantly with aggressive clinicopathologic characteristics, including advanced tumor grade and poor prognosis. Studies with cultured cells indicated that EIF3B knockdown inhibited HCC cell invasion and metastasis by depressing the epithelial-mesenchymal transition (EMT). EIF3B also activated the TGFBI/MAPK/ERK signaling pathway by increasing the levels of pMEK and pERK. Conclusions: Our results indicate that EIF3B functions as an oncogene in HCC that accelerates cell invasion, metastasis, and the EMT by stimulation of the TGFBI/MAPK/ERK signaling pathway. EIF3B is a potential target for the treatment of HCC.